Vulnerability assessment of churches under earthquake hazard - Esmeralda Paupério (2013)
The development of a framework for the quantification of the seismic vulnerability of churches is presented. Given the advantages of having different areas of expertise contributing for the assessment of vulnerability, the proposed framework involves a multidisciplinary approach for the definition of the vulnerability of churches. The general scope and the conceptual definition of the proposed framework are discussed and it is established that vulnerability assessment must be carried out with respect to three fundamental components: the building, the collections and the building surroundings. Implementation details of the framework are then presented for the specific case of church heritage under seismic hazard. The applicability of the vulnerability assessment approach is illustrated using real case scenarios.